Experimental and analytical study on the stability of a low aspect ratio single-phase natural circulation loop coupled to a parabolic trough collector. (May 2023) - Nakul, S.; Arunachala, U.C.; Vijayan, P.K.
Abstract: Use of passive heat transport systems in renewable energy eliminates operator and external power requirements, thereby reducing the cost. Hence, a horizontal heater and horizontal cooler rectangular natural circulation loop (NCL) of low L/D (110) and aspect ratio (0.54) is coupled to a parabolic trough in the present work. Experimental investigations of the loop's steady state and stability characteristics were carried out at various powers corresponding to the solar irradiances using water as the heat transfer fluid. SolTrace was used to determine the heat loads at different direct normal irradiance (DNI) for the selected loop and trough dimensions. The upper threshold for stability was experimentally observed for the first time and reported here. Stability analysis carried out for different loop diameters revealed that the power at which the upper threshold of instability occurs reduces significantly with increase in loop diameter, enabling its observation in the low-pressure low temperature loop employed in the present study. Stabilizing techniques like orifice insertion and loop inclinations were also studied in detail. The results showed stability at higher heat loads (> 350 DNI), while the instability at lower heat loads can be curbed using an orifice (β = 0.5) or a loop inclination (> 4°). The small inclination can eliminate multiple steady state solutions and hence stabilizes the loop. Besides, the reduction in natural circulation flow rate with inclination is much smaller compared to the orifice making its heat transport capability higher. Additionally, the steady state results were validated with 1-D analytical model giving a good match. Graphical abstract: Unlabelled Image Highlights: Aptness of large diameter, low aspect ratio NCL to PTC is experimentally explored. Linear stability analysis and 1-D theoretical model are compared with the findings. Application of orifice and loop tilt techniques for flow stabilization. The upper threshold for stability is experimentally found and validated.